ضوابط استخدام مبدأ الضرورة العسكرية في النزاعات الدولية المسلحة - حوبة, عبد الغني (University Of El-Oued, 2020)
تناولت هذه الدراسة ضوابط استخدام مبدأ الضرورة العسكرية في النزاعات المسلحة الدولية في الفقه الإسلامي والقانون الدولي الإنساني في مقدمة وبابين، وخاتمة،ركزت في الباب الأول على الشق النظري، فبدأت بمفهوم مبدأ الضرورة العسكرية كأحد أهم مبادئ القانون الدولي الإنساني في النزاعات المسلحة الدولية،إذ ميزته عن الحالات المشابهة له، وبينت مشروعيته وطبيعته القانونية ومقداره ثم عرضت أسسه ومصادره في الفقه الإسلامي والقانون الدولي الإنساني،وانتقلت بعدها في الباب الثاني لدراسة الضوابط العملية في استخدام الضرورة العسكرية القتالية وغير القتالية من خلال نصوص الفقه الإسلامي، وكذا وضحت شروط قيامها والقيود الواردة عليها في صكوك القانون الدولي الإنساني،ثم تناولت تطبيقات على مبدأ الضرورة العسكرية في النزاعات المسلحة الدولية في الفقه الإسلامي،وذلك من خلال القتال ردا للعدوان وقتل النساء والصبيان و حالة التترس وقطع النخل و الشجر و ذبح الحيوان ثم صلاة الخوف،وأما بالنسبة للقانون الدولي الإنساني،فقد ذكرت حالات الاستناد للضرورة وحالات انتفاءها بالنسبة للمدنيين والأعيان المدنية،ثم قدمت نموذجا تطبيقيا في الممارسة التطبيقية أبرزت فيه مدى مخالفة الاحتلال الإسرائيلي لضوابط استخدام مبدأ الضرورة العسكرية في قطاع غزة، وبينت مدى وقوع المسؤولية الدولية عن انتهاك قواعد القانون الدولي الإنساني،وخلصت في النهاية لخاتمة تم فيها استعراض أهم نتائج البحث و اقتراحاته. The study examined the criteria of military necessity in international armed conflicts through Islamic jurisprudence and international humanitarian law, it has been presented with an introduction, two chapters and conclusion. in the first chapter we focused theoretically on the concept of the principle of necessity as one of the most important principles of international humanitarian law in international armed conflicts in sense of distinguishing it from the similar cases, secondly, we presented its foundations and its sources from Islamic jurisprudence then, the study had been moved to the criteria of the using military necessity, combat and non-combat through the texts of Islamic jurisprudence, as well as the conditions of the establishment and restrictions contained in the instruments of international humanitarian law, in addition to The application of the principle of military necessity in international armed conflicts in the Islamic jurisprudence through fighting in response to aggression and the killing of women and boys and the state of harassment and and cutting of palm trees and slaughter of animals, then the prayer of fear moreover, international humanitarian law used to mention the cases of necessity and cases of absence cencerningCivilians and civilian objects after that the study had been provided by an application model which was the violation of the Israeli occupation to the criteria of military necessity which led to the international responsibility for violating the rules of international humanitarian law.
أطروحة دكتوراه في العلوم الإسلامية تخصص شريعة و قانون
Keywords: القانون الدولي الإنساني،الضوابط، الضرورة العسكرية، النزاعات الدولية المسلحة، المسؤولية الدولية.; the international humanitarian law, criteria, military necessity, international armed conflicts, international responsibility